2019
DOI: 10.1111/btp.12724
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the demographics and behavior of bearded pigs (Sus barbatus) across a land‐use gradient

Abstract: Beyond broad‐scale investigations of species diversity and abundance, there is little information on how land conversion in the tropics is affecting the behavior and demographics of surviving species. To fill these knowledge gaps, we explored the effects of land‐use change on the ecologically important and threatened bearded pig (Sus barbatus) over seven years in Borneo. Random placement of camera traps across a land‐use gradient of primary forest, logged forest, and oil palm plantations (32,542 trap nights) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…Related to this, we need to understand what physiological and behavioral strategies species adopt to cope with or evade unfavorable microclimates. For instance, mobile species might shift from diurnal to nocturnal activity to escape warmer temperatures (Davison et al, 2019;Levy et al, 2019), while sessile organisms such as plants can thermoregulate by increasing transpiration and adjusting leaf angles (Fauset et al, 2017). Alternatively, some species may be able to rapidly acclimate and/or adapt to novel microclimates, as was recently shown for a poison frog in Costa Rica that exhibits higher preferred body temperatures in forests that have been logged (Rivera-Ordonez et al, 2019).…”
Section: Species Distributions and Population Dynamicsmentioning
confidence: 99%
“…Related to this, we need to understand what physiological and behavioral strategies species adopt to cope with or evade unfavorable microclimates. For instance, mobile species might shift from diurnal to nocturnal activity to escape warmer temperatures (Davison et al, 2019;Levy et al, 2019), while sessile organisms such as plants can thermoregulate by increasing transpiration and adjusting leaf angles (Fauset et al, 2017). Alternatively, some species may be able to rapidly acclimate and/or adapt to novel microclimates, as was recently shown for a poison frog in Costa Rica that exhibits higher preferred body temperatures in forests that have been logged (Rivera-Ordonez et al, 2019).…”
Section: Species Distributions and Population Dynamicsmentioning
confidence: 99%
“…Recent ecological evidence from Sabah suggests substantial rates of bearded pig crop raiding in oil palm plantations (Love et al 2018, Davison et al 2019, which was widely reported amongst our respondent pool as well. We therefore hypothesize that bearded pigs in many parts of Sabah are employing a "high risk, high reward" strategy of feeding on cross-border oil palm fruit subsidies, providing access to high-fat food resources but also elevating risk due to human hunting in oil palm plantations, potentially causing elevated flight responses in pigs.…”
Section: Perceived Changes In the Behavioral Ecology Of Bearded Pigsmentioning
confidence: 55%
“…increasing the proportion of young pigs in plantations), and changing activity patterns (e.g. shifting pigs to nocturnal activity patterns in plantations) (Love et al 2018, Davison et al 2019. Research has also shown how bearded pigs benefit from crop-raiding in oil palm plantations (Love et al 2018, Davison et al 2019, and has hypothesized that this behavior could potentially increase their populations near oil palm plantations (Luskin et al 2017, Love et al 2018, Davison et al 2019.…”
Section: Historical and Contemporary Bearded Pig Hunting Practices Inmentioning
confidence: 99%
“…increasing the proportion of young pigs in plantations) and changing activity patterns (e.g. shifting pigs to nocturnal activity patterns in plantations) (Davison et al, 2019;Love et al, 2018). Bearded pigs also receive food subsidies from crop-raiding within oil palm plantations (Davison et al, 2019;Love et al, 2018), and it has been hypothesized that this behaviour could potentially increase wild pig populations near oil palm (Davison et al, 2019;Love et al, 2018;Luskin, Brashares, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%